Identification of Bullying Behaviour Tendencies among Senior High School Students - Christiana, Elisabeth (Universitas Negeri Padang, 2024)
Bullying constitutes a form of violent conduct involving psychological or physical aggression directed towards individuals or groups perceived as weaker, through words, physical actions, or direct contact, which occurs recurrently. Such behaviour appears to be an enduring issue that considerably unsettles students. This is attributable to the potential long-term effects, including fear, diminished confidence, emotional regulation difficulties, persistent sadness, and trauma. Bullying manifests in various modalities, such as verbal, physical, relational, and cyberbullying. The research methodology employed in this study adopts qualitative approaches, primarily through observation. In the course of these observations, the researcher directly engaged with the subjects, monitoring their behaviours and interactions within the peer environment at school. The participants of this study were high school students enrolled at SMAN 1 Driyorejo Gresik. Data collected from research conducted among students at SMAN 1 Driyorejo indicate that 35.7% of students tend to engage in bullying behaviour, notably cyberbullying. Furthermore, 28.7% of students demonstrate tendencies towards verbal bullying, 18.9% towards relational bullying, and 16.5% towards physical bullying.